PREDIKSI INDEK HARGA KONSUMEN KOTA MALANG DENGAN MODEL EXPONENSIAL SMOOTHING-STATE SPACE - Sigit Setyowibowo; Mohamad As’ad; sujito; Eni Farida (Sekolah Tinggi Manajemen Informatika & Komputer PPKIA Pradya Paramita Malang, 2022)
The consumer price index (CPI) is an important variable in calculating inflation. CPI and inflation are two very closely related variables in the economic development of a country or region. Predictions of CPI and inflation are very important to see economic developments related to investment, development planning, or anything related to planning management which is usually used as a reference in making decisions. The purpose of this study is to predict the CPI of Malang City with a simple model without any statistical assumptions that are sometimes difficult to fulfill. Consumer price index (CPI) data used is secondary data obtained from the website of BPS Malang. CPI data used is from January 2005 to November 2021. This study uses four exponential smoothing models, namely single exponential smoothing (SES), double exponential smoothing (DES) from Holt's, triple exponential smoothing (TES), and single exponential smoothing- state space (ETS). The ETS model used is ETS(M, N, N). The ETS(M, N, N) model means a single exponential smoothing model with multiplicative error. The best model obtained from this research is ETS(M, N, N). The determination of the best model in this study is based on the minimum Akaike information criteria (AIC) and Bayesian information criteria (BIC) values.